IN SILICO DESIGN, SYNTHESIS AND EVALUATION OF IN VITRO GLUCOSE UPTAKE, GENE EXPRESSION, AND α-GLUCOSIDASE INHIBITORY ACTIVITY OF NOVEL 2-AMINOBENZIMIDAZOLE DERIVATIVES - SREEJA S; ANTON SMITH A; MATHAN S (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study was aimed to design and evaluate the antidiabetic potential of novel 2-aminobenzimidazole derivatives by in silico method. Materials and Methods: Various in silico tools such as Chemsketch, Molinspiration, Prediction of activity spectra for substances, OpenBabel, Discovery Studio was used in the designing and evaluation of the biological activity. The retrieved hits were further filtered by absorption, distribution, metabolism, and excretion descriptors. The designed molecules having required physicochemical properties, drug-likeness, and obeying Lipinski’s rule of five were selected for the synthesis. The synthesized compounds were subjected to determination of yield, melting point and characterized by infrared, 1HNMR, 13CNMR, and mass spectroscopic methods. The selected derivatives were subjected to in vitro glucose uptake, 50% lethal dose (LD50) determination, gene expression analysis, and α-glucosidase inhibitory assay. Results: Totally, 32 novel analogs of 2-aminobenzimidazole were designed and 17 compounds were selected for docking analysis; and finally, five derivatives (3a, 3c, 3e, 3f, and 3h) were selected for synthesis. Among them, the compounds 3a and 3f were selected for in vitro glucose uptake analysis. Finally, the compound 3f was selected for LD50 determination, gene expression analysis, and α-glucosidase inhibitory assay. The selected derivative 3f showed a significant α-glucosidase inhibitory activity compared with the standard drug acarbose. Conclusion: These results are useful for further investigation in the future, and hopefully, these studies could discover a new specific leads in antidiabetic category as α-glucosidase inhibitor.